1943
DOI: 10.1042/bj0370572
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial action of some stilbene derivatives

Abstract: Early types of antibacterial substances were not specifically antibacterial, but were usually toxic to all living cells, and were of value only in so far as they could be employed without serious damage to the host. The search for more suitable antibacterial agents resulted in the preparation and testing of many substances of widely different constitution, and it was from the empirical yet systematic investigations of one such class of chrysoidine dyestuff that knowledge of the activity of sulphanilamide arose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1945
1945
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…In confirmation of the observations of Faulkner (1943) and Brownlee, Copp, Duffin & Tonkin-(1943) on other Gram-positive bacteria, we found that both diethyl stilboestrol and hexoestrol, in amounts of 160,ug./10 ml., inhibited the growth of L. helveticus. The action of these compounds could not be reversed by the addition of lecithin or cholesterol.…”
Section: I945supporting
confidence: 73%
“…In confirmation of the observations of Faulkner (1943) and Brownlee, Copp, Duffin & Tonkin-(1943) on other Gram-positive bacteria, we found that both diethyl stilboestrol and hexoestrol, in amounts of 160,ug./10 ml., inhibited the growth of L. helveticus. The action of these compounds could not be reversed by the addition of lecithin or cholesterol.…”
Section: I945supporting
confidence: 73%
“…An extensive interest in the antifungal property of gonadal hormones probably originated in clinical preoccupation with the influence of pregnancy and menstruation on the incidence in severity of infectious diseases in man. As early as 1935 estrogens were reported to have antibacterial activity (7)(8)(9). There is now considerable evidence that a large number of steroids have antimicrobial effects in vitro on bacteria, molds, yeasts and protozoa (see reference 5 and 6 for review).…”
Section: Discussionmentioning
confidence: 99%
“…Anthracene, 1,2-benzanthracene, and phenanthrene at 0.1 per cent levels and cyclohexane and benzene vapors were generally unsatisfactory. At 0.1 per cent, stilbestrol, reportedtobe antibacterial by Brownlee et al (1943), allowed no growth.…”
Section: Resultsmentioning
confidence: 96%